CFD simulation of gas–liquid flows in stirred vessel equipped with dual rushton turbines: influence of parallel, merging and diverging flow configurations - Khopkar, Avinash R.; Tanguy, Philippe A. (Chemical engineering science, 2008)
Computational fluid dynamics (CFD) was used to investigate the influence of parallel, merging and diverging flow configurations on the gas dispersion operation in stirred vessel. The simulation was based on the two-fluid model along with the standard k– ε turbulence model along with an appropriate drag correction to account for bulk turbulence [Khopkar, A.R., Ranade, V.V., 2006. CFD simulation of gas–liquid stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal 52, 1654–1671]. The model predictions were compared with the published experimental data of Bombac, Zun [2000. Gas-filled cavity structures and local void fraction distribution in vessel with dual-impellers. Chemical Engineering Science 55, 2995–3001] for parallel flow configuration. The predicted results show reasonably good agreement with the experimental data. The computational model was then used to simulate the gas–liquid flows for the other two flow configurations. The results of this work provide ‘a priory’ information on the implications of flow configuration on the vessel performance.